Intrahousehold Commitment and Intertemporal Labor Supply - Pierre-André Chiappori; J. Ignacio Gimenez-Nadal; José Alberto Molina; Alexandros Theloudis; Jorge Velilla (Institute of Labor Economics (IZA), 2020)
This paper studies household labor supply, within the context of an intertemporal collective model, and three prominent intrahousehold commitment regimes: full commitment, no commitment, and limited commitment. We propose a test that distinguishes among all three alternatives based on how contemporary and historical changes to the economic environment affect household behavior. We implement the test on recent data from the Panel Study of Income Dynamics in the US (1999-2017). Although couples and singles behave similarly in many aspects, couples' labor supply exhibits distinctive features that are consistent with limited commitment. We then use our results to highlight several issues and caveats that arise when testing for commitment.
Keywords: D15; J22; 330; intertemporal collective model; household labor supply; commitment; PSID